Advanced Electro‐Oxidation with Boron‐Doped Diamond for Acetaminophen Removal from Real Wastewater in a Microfluidic Reactor: Kinetics and Mass‐Transfer Studies. Issue 11 (13th May 2019) - Mousset, Emmanuel; Puce, Marta; Pons, Marie‐Noëlle
Abstract: The removal of hazardous organic micropollutants in municipal wastewater treatment plants (WWTP) has become a common concern for public decision‐makers and stakeholders. An advanced electro‐oxidation with boron‐doped diamond (BDD) anode material is proposed to remove acetaminophen as a representative micropollutant in synthetic solution. A customized microfluidic reactor was run in batch mode, and the main operating parameters (i. e. current density, interelectrode distance and solution conductivity) were optimized by minimizing the energy requirement. An optimal current density of 4 mA cm −2 and an optimal interelectrode distance of 500 μm were newly obtained and explained. Mass transport limitation was observed at lower gaps, with a 3.4‐fold decrease in the mass transfer coefficient from 500 μm to 50 μm intervals. In addition, the kinetics of degradation decreased dramatically after a certain electrolysis time. This was attributed to the increase in gas bubble production with treatment time. An increase in the solution conductivity from 0.23 to 2.0 mS cm −1 increased the degradation rate efficiency twofold and decreased the specific energy from 0.88 to 0.17 kWh g −1 at 85 % acetaminophen decay yield. The influence of a real matrix from low‐conductivity reclaimed WWTP (0.86 mS cm −1 ) highlighted slightly lower kinetics of degradation, but similar energy efficiency until 60 % of pollutant degradation and higher energy efficiency than in conventional macro‐reactors. Abstract : Treat it right : The boron‐doped diamond (BDD) anode is implemented in an electrochemical microfluidic cell for the electrocatalytic treatment of acetaminophen in synthetic and reclaimed wastewater. An optimal interelectrode distance can be determined at optimal mass transfer and optimal decay rate constant. The low conductivity of reclaimed wastewater can be treated with the same range of energy requirement than the synthetic solution. The energy efficiency can be maximized with a short interelectrode gap in order to minimize the negative impact of the low conductivity of solutions.